SMALL MAMMALS TRAPS IN COASTAL LOWLAND FOREST AND GARDENS OF YONGSU, PAPUA - Pattiselanno, Freddy; Arobaya, Agustina Y. S. (Department of Forest Resources Conservation and Ecotourism - IPB University, 2018)
A study was conducted in Yemang, Yongsu Dosoyo –at the northern site of Cyclops moutains, in Depapre District, Jayapura, Papua. Twenty-four traps were randomly set in 4 trap stations per habitat (garden and forest) with 10 m distance between stations. Each trap stations consist of three traps with three different type of baits during four on four consecutive nights. This paper presents results of this study. Key words: small mammals, lowland forest, garden, Papua